Decision Model for the Media Selection - Tatjana Kozjek; Vladislav Rajkovič; Marko Ferjan (Central European Public Administration Review)
The article presents the decision model for choosing the media in the performance of public relations (PR). The core of the model lies in the use of modern information methods with the accent on the artificial intelligence methods in decision-making processes which allow transparency and simple explanation of the decision knowledge and of the decision itself. The framework of the solution is the description of the realization of the model with the support of the DEXi system. The model covers the qualitative and the quantitative measures for the final choice. This allows a more wholesome overview of the media and of the goals the decision aims to achieve. The determined fundamental elements of the model are: the target public, the goals the organization aims to achieve via public relations, the resources assigned to the public relations, the messages to transmit to the public, etc. The criteria which form constituent parts of the decision model have been designed on the basis of public relations literature study and the practical experience of the Faculty.